P997Risk of stroke and mortality in patients with atrial fibrillation and insulin dependent versus non-insulin dependent diabetes mellitus. (18th June 2020) - Barrett, O; Kezerle, L; Westreich, R; Avgil Tsadok, M; Akriv, A; Feldman, B; Leventer-Roberts, M; Ohana, R; Haim, M
Abstract: Funding Acknowledgements: Pfizer pharmaceutical corporation Background: Diabetes is a known risk factor for thromboembolic events in patients with non-valvular atrial fibrillation (NVAF). Whether patients on insulin therapy are at an increased risk for stroke compered to patients treated solely by oral antidiabetic medications is not yet established. Aim: To assess the risk of ischemic stroke and mortality in patients with NVAF and diabetes mellitus (DM) treated by insulin vs. oral antidiabetic treatment. Methods: A prospective, historical cohort study based on the Clalit Health Services (CHS) electronic medical records database, including all individuals age ≥ 21 years with a first diagnosis of NVAF between January 2010 to December 2016 and a minimal follow-up period of 1 year. Patients were divided into two groups based on their diabetes therapy regiment (insulin vs. oral antidiabetic medications). Results: Overall study population included 12, 231 patients with AF and DM, of them 3510 (28.7%) had an insulin-requiring diabetes. The median age was 72.4 years (IQR 65-80) in the insulin- treated group and 75.2 (IQR 68-83) in the orally treated group, with a slight majority of women in both groups, 51.6% and 53.5% respectively. Patients in the insulin group had significantly higher co-morbidity rates including hypertension (HTN) (93.6% vs. 91.2%; p < 0.001), congestive heart failure (CHF) (38% vs. 22.2%%; p < 0.001), previous cerebrovascular accident/ transient ischemic attack (CVA/TIA) (23.1% vs.14.5%;  p < 0.001) and vascular diseases (62.1% vs. 46.5%; p < 0.001). Moreover, patient on insulin therapy were significantly less treated with anticoagulation medications at baseline compered to patients not treated with insulin (38.9% vs. 46.6%; p < 0.001). The incidence of stroke per 100 person-years was 2.62 in the insulin-treated group and 2.02 in the oral-treated group. Although, diabetes patients on insulin therapy had a significantly increased risk for stroke compared to patients not treated with insulin in the univariate analysis (HR: 1.34; 95%CI: 1.13- 1.60), this association was not found to be significant after adjusting for confounding variables (HR: 1.17; 95%CI: 0.96- 1.41). The rate of mortality per 100 person-years was 19 in the insulin-treated group and 12.6 in the oral-treated group. The risk for overall mortality was significantly higher in the insulin-treated group compared to the non-insulin group (HR: 1.38; 95%CI: 1.29- 1.48), as found in the multivariate Cox model, adjusted for age, gender, Creatinine clearance, HTN, CHF, CVA/TIA, vascular diseases, duration of diabetes and use of anticoagulation therapy. Conclusion: In this cohort of patients with newly diagnosed NVAF and DM, patients on insulin are at increased risk of all cause mortality and a have a trend of increased risk of stroke after accounting for other recognized risk factors for stroke and mortality in this population.